Pengaruh Harga Minyak Dunia, Inflasi, Konsumsi Rumah Tangga terhadap Pertumbuhan Ekonomi Indonesia - Ulin Nuhaella Almaya; Wahyu Hidayat Rianto; Syamsul Hadi (Program Studi Ekonomi Pembangunan, 2021)
This study aims to determine the effect of world oil prices, inflation, and household consumption on economic growth in Indonesia. This research is a type of descriptive research with a quantitative approach using the annual time series in 1988-2018. The analysis technique used in this study is multiple linear regressions with 31 samples. The results showed that both simultaneously and partially, world oil prices and inflation had a significant (negative) effect and household consumption had a significant (positive) effect on economic growth. Based on research results, the government can improve and build oil and gas infrastructure so that it can optimize oil production. This is very useful because it will reduce oil imports and also reduce the inflation rate. The government can also establish monetary policy and fiscal policy to maintain inflation stability. Other policies that can be done are by increasing the amount of goods produced so that the number of goods in circulation increases, setting maximum prices for several types of goods, and also making policies that can control the inflation rate so as to encourage domestic consumption due to price stability, so that consumption expenditure can be increase or can be stable